Analysis of the Application of the Picture and Picture Learning Model in View of the Activeness of Students in the Science Subject of Grade IV Elementary School - Rukmana, Maissy Diana; Faradita, Meirza Nanda; Mirnawati, Lilik Binti (Universitas Trunojoyo Madura, 2023)
This study aims to analyze the application of the picture and picture learning model seen from the activeness of students. This type of research uses descriptive qualitative research methods with semistructured interview techniques. Data collection techniques used interview instruments given to class IV teachers and instruments distributed to observers to observe the activities of fourth grade students at SD Muhammadiyah 19 Surabaya. Based on the results of teacher interviews, the use of the picture and picture learning model makes students active in the learning process. Meanwhile, based on the results of the activity questionnaire, the average student from observations made by the observer obtained a percentage of 87.74% in the very active category, indicating that the results of student activities obtained a percentage of 81% -100%, being very active . It can be concluded that the picture and picture learning model makes students active in learning.